Association Between Genetic Variant in the Promoter of Pri-miR-34b/c and Risk of Glioma - Li, Jinghui; Liu, Xiaoyu; Qiao, Yu; Qi, Renli; Liu, Shunjin; Guo, Jing; Gui, Yang; Li, Juanjuan; Yu, Hualin (Frontiers in Oncology, 2018)
Growing evidence indicates that p53 can regulate the expression of miRNAs, especially the miR-34 family members, which are described as potential tumor suppressors. Loss of miR-34 impairs TP53-mediated cell death, whereas over expression of miR-34 induced apoptosis. The study aimed to investigate the association between the pir-miR-34b/c rs4938723, TP53 Arg72Pro and the risk of glioma. We genotyped the two polymorphisms in175 glioma patients and 235 healthy controls using polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) and DNA sequencing assay.We found that the CC genotype of the pir-miR-34b/c rs4938723 was associated with a significantly decreased risk of glioma compared to the TT genotype (CC vs. TT: adjusted OR=0.43；95% CI, 0.21-0.87，P = 0.02).Moreover, a significant association between the patients with glioma and controls was also observed in a recessive model (OR = 0.41; 95 % CI, 0.21–0.81, P = 0.007).In contrast, the CC genotype of theTP53 Arg72Prowas associated with a significantly increased risk of glioma compared to the GG genotype (CC vs. GG: adjusted OR=1.73；95% CI, 1.04-2.89，P=0.04), and a significant association between the patients with glioma and controls was also observed in a recessive model (OR= 2.00; 95% CI, 1.26–3.18, P=0.003). These findings suggest that the pri-miR-34b/c rs4938723CC and TP53 Arg72-Pro polymorphisms may be associated with the risk of glioma.